2014
DOI: 10.1160/th13-10-0827
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of venous thrombosis in children with cancer

Abstract: SummaryThere has been an extensive body of research focusing on the epidemiology of thrombosis in adult cancer populations; however, there is significantly less knowledge about thrombosis in paediatric cancer populations. Thrombosis is diagnosed with increasing frequency in children being treated for cancer, and there is an urgent need to increase our understanding of the epidemiology of thrombosis in this population. Currently, there are no guidelines for identification of high-risk groups, prophylaxis or man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 45 publications
2
24
0
3
Order By: Relevance
“…Among pediatric patients, adolescents were reported to have the highest incidence of VTE at 94 cases per 10,000 hospital admissions, and those with a malignancy had the highest rate of first time and subsequent VTE. [11][12][13][14][15] A similar trend has been reported in the adult literature, with a notable increase in the rates of VTE in adults with cancer over the last several decades. 16 Approximately 20% of reported cases of VTE among adults occur in patients with cancer.…”
Section: Epidemiologysupporting
confidence: 57%
“…Among pediatric patients, adolescents were reported to have the highest incidence of VTE at 94 cases per 10,000 hospital admissions, and those with a malignancy had the highest rate of first time and subsequent VTE. [11][12][13][14][15] A similar trend has been reported in the adult literature, with a notable increase in the rates of VTE in adults with cancer over the last several decades. 16 Approximately 20% of reported cases of VTE among adults occur in patients with cancer.…”
Section: Epidemiologysupporting
confidence: 57%
“…4,40 The molecular landscapes of pediatric brain tumors are vastly different than those in adults and are increasingly well characterized, 78,[91][92][93] but they are infrequently discussed in the context of CAT. 38,94,95 While this is understandable due to a lesser clinical burden of thrombosis in children, the biological effects of hemostatic perturbations are likely relevant. For example, in pediatric medulloblastoma (MB), the expression of TF, PAR-1, FX, and other elements of the vascular coagulome and angiome is highly divergent between the four main disease subtypes: sonic hedgehog (SHH), wingless (WNT), group 3, and group 4.…”
Section: Oncogenic Events and Brain Tumor Coagulomementioning
confidence: 99%
“…Studies using radiological screening to diagnose asymptomatic thromboses have identified rates of up to 40% (Mitchell et al , ; Albisetti et al , ), although the significance of many of these asymptomatic events is unclear. The incidence of symptomatic VTE varies according to cancer subtype, being more common in acute lymphoblastic leukaemia (ALL) (5% from a meta‐analysis published in 2006, range 3–14%), sarcoma (7–13%) and lymphoma (2–17%) and less common in children with other malignancies (Caruso et al , ; Nowak‐Göttl et al , ; Piovesan et al , ; Van Ommen & Chan, ).…”
Section: Assessing the Risk Of Venous Thromboembolism (Vte)mentioning
confidence: 99%